Using mechanical experiments to study ground stone tool use: Exploring the formation of percussive and grinding wear traces on limestone tools - Paixao, Eduardo (2021)
Ground Stone Tools (GSTs) have been identified in several Levantine archaeological sites dating to the Middle Paleolithic. These tools, frequently made of limestone, are often interpreted based on their morphology and damage as having been used for knapping flint, and sometimes as well for breaking animal bones or processing vegetal materials. However, the lack of experimental referential on limestone is a major obstacle for the identification of diagnostic traces on these types of tool and raw material. In this sense, the understanding of the specific function of these GST and the association between tool types and activity remains often unknown or merely speculative. Recent discoveries at the site of Nesher Ramla revealed one of the largest Middle Paleolithic assemblages of limestone GST. Our use-wear analysis has identified several types of both macro and micro-wear traces on different tools. Such diversity highlights the need for developing an experimental reference collection that can enable detailed comparison between experimental and archaeological use-wear evidence. In this paper, we present the results of mechanical experiments specially designed to understand and quantify major characteristics of macro and micro use-wear traces on limestone GST, as a result of 3 main activities: animal bone breaking, flint knapping and grinding acorn. This study pursues 3 main goals: a) improving our ability to distinguish natural from anthropogenic alterations on limestone b) identifying and characterizing differences between wear-traces (macro and micro), and c) building a reference collection for thorough comparisons of use-wear and residues. Our results indicate that it is possible not only to identify anthropogenic alterations but also to specifically distinguish the use-wear traces formed on limestone as result of percussive activities of bone and flint, even under controlled experiments allowing to keep variables other than the worked material constant.. This study aims to contribute toward establishing an experimental library of use-wear traces on limestone. Primarily, this results directly supports the analyses of Middle Paleolithic assemblages from the Levant yet can also be of relevance to studies concerned with other regions and periods.